Riscos demográficos e atuariais nos planos de benefício definido e de contribuição definida num fundo de pensão - Ricardo Pena Pinheiro (2005)
The focus of this dissertation is to assess the actuarial and demographics risks involved in the mathematical reserves of programmed retirement benefits offered in defined benefit and defined contribution plans administrated by a brazilian pension fund. Therefore, it is a micro-demographic analysis of the changing effects in the demographic variables such as mortality rate, disability, withdraw and participant entry in the retirement plans in relation to the mathematical reserves of benefits yet to be paid and already paid, which are necessary to support the payment of programmed retirement benefits offered by a closed entity of a complementary scheme. Another dimension assessed in this work is concerned with the demographics and economics implications in relation to the process of preference change from defined benefit plans to defined contribution plans in the pension fund environment, focusing the risks involved and the choices made by participants and sponsors. Based on the methodology of the simple and multiple decrements tables, this work examined the impacts in the assumption modifications regarding demographic variables on the mathematical reserve of retirement benefits and pensions. The results indicated that the probability of annual permanence of the participant in the benefit plan of the pension fund reflects, according to the multiple decrements table, the exposure to exit risks due to various decrements that operate jointly and compete against each other, imposing costs of the programmed retirement benefits on the retirement plans of the pension funds, with lower levels when compared to the simple decrement table in which the decrements act in an isolated way. Finally, this thesis presents the actuarial flow for defined benefit and defined contribution plans administrated by the pension fund under analysis, with basis on the population and financial projections on a thirty-year span so as to orientate the resource allocation decisions, aiming at risk reduction, of eventual actuarial deficits related to the stock mismatch and cash flow in the retirement plans, for participants and the sponsoring company.